The Effect of Application of Command Teaching Style on Under Passing Skills in Games Volleyball in Minahasa Volleyball Athletes - Jan Lengkong (Researchparks Publishing, 2023)
This study aims to examine the application of the commando teaching style to the improvement of lower passing skills in volleyball games. The method used in this research is the experimental method. The sample used was Minahasa volleyball athletes totaling 20 samples, which were divided into two groups, namely the experimental group with the command teaching style totaling 10 samples and the control group which did not receive treatment totaling 10 samples. The research was carried out for one month with a frequency of three times a week. The research design used was